Dominant Factors Affecting Employee Performance in Hospitals: A Systematic Literature Review - Suyatno, Endi; Tukiran, Martinus (PT FORMOSA CENDEKIA GLOBAL, 2023)
Hospitals are an integral part of the entire health service system that serves patients with various types of services. The success of health services in hospitals cannot be separated from various service factors. Therefore, in order to continue to develop itself and for the survival of the organization, hospital management needs to improve employee performance. This research uses a systematic review method. The data source for this research was obtained through literature searches on the internet via the published Garuda Portal and Google Scholar databases. A total of 16 articles were included in the systematic review. The aim of this research is to conduct a systematic review of the Dominant Factors that Influence Employee Performance in Hospitals. Compensation, leadership style, motivation and job satisfaction have a positive effect on performance. As compensation increases, motivation and job satisfaction will also increase performance.